Pathogenic Fungi Associated with Soursop Fruits (Annona muricata L.) during Postharvest in Nayarit, Mexico - Alejandra Verónica González-Ruíz (MDPI AG, 2021)
Nayarit ranks first in national soursop production (Annona muricata L.). However, the soursop fruits are perishable and susceptible to microorganisms attack, reaching up to 60% of the postharvest losses. Due to the previously mentioned points, the objective of the present study was to isolate, identify, and determine the pathogenicity of fungi related to postharvest diseases in soursop fruits in the main producing areas of Nayarit, Mexico. Several fungi belonging to the genera Fusarium sp., Rhizopus, Lasiodiplodia, Gliocladium, and Colletotrichum were isolated and morphologically identified. Further, bioinformatics sequence analysis of the ITS1-5.8S-ITS2 region of the rDNA identified that most pathogen species were Lasiodiplodia theobromae, Lasiodiplodia pseudotheobromae, and Nectria haematococca, which cause postharvest diseases in soursop fruit, affecting their quality. Lasiodiplodia causes the highest postharvest damage in soursop among the pathogenic species identified.